2010
DOI: 10.1007/s00380-010-0074-4
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography evaluation of coronary plaque morphology in patients with stable angina

Abstract: The purpose of this study was to evaluate the morphology and composition of atherosclerotic coronary plaques in patients with stable coronary artery disease by 64-row multidetector computed tomography (CT) angiography. A total of 56 patients were divided into an ischemia-related (n = 31) and a nonischemia-related lesion group (n = 25) based on myocardial perfusion scintigraphy, invasive angiography, and 1-year clinical follow-up. The 56 lesions detected by CT imaging were analyzed; the severity of stenosis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Whereas in other studies the calcification process was investigated in vitro and in animal models (rats) being fed with vitamin D and nicotine [6,23], the present study was performed in subjects with normal renal function and balanced calciumphosphate homeostasis. Another difference is the technique applied for the evaluation of calcification processes, which was atomic absorption spectrophotometry in invitro studies [6,21] and 64-MSCT imaging in our study, which is the gold standard technique for the non-invasive evaluation of the CACS in various clinical settings [24][25][26]. Our study is limited by the small samples size.…”
Section: Discussionmentioning
confidence: 74%
“…Whereas in other studies the calcification process was investigated in vitro and in animal models (rats) being fed with vitamin D and nicotine [6,23], the present study was performed in subjects with normal renal function and balanced calciumphosphate homeostasis. Another difference is the technique applied for the evaluation of calcification processes, which was atomic absorption spectrophotometry in invitro studies [6,21] and 64-MSCT imaging in our study, which is the gold standard technique for the non-invasive evaluation of the CACS in various clinical settings [24][25][26]. Our study is limited by the small samples size.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, characterization of a coronary plaque causing mild-to-moderate stenosis is a clinically important role of coronary CTA for appropriate patient management. The CT number of a soft plaque (unstable plaque) is approximately ≤40 HU (32) and that of a fibrous plaque (stable plaque) is 80–100 HU (7). Our phantom study results (50% stenosis model with 40-HU plaque) suggested that the non-calcified plaque changed subtype from soft/lipid-rich to fibrotic with FBP and AIDR3D.…”
Section: Discussionmentioning
confidence: 99%
“…In July 2011, we reported the coronary CT angiography (CCTA) imaging features of ischemia-related coronary plaques in patients with stable angina on 64-row multidetector CT [1]. We used the univariate and multivariate logistic regression analysis to identify which clinical characteristics and CT imaging findings were useful to differentiate ischemia-related lesions from nonischemia-relate lesions.…”
Section: Short Commentarymentioning
confidence: 99%